2
$\begingroup$

Question: Solve the following simultaneous equations for real values of x and y $$ \left\{ \begin{array}{l} 9^{2x+y} - 9^x \times 3^y = 6 \\ \log_{x+1}(y+3) + \log_{x+1}(y+x+4) = 3 \end{array} \right. $$

What I have attempted; for the first equation $$ 9^{2x+y} - 9^x \times 3^y = 6 \\ 9^{2x+y} - 3^{2x} \times 3^y = 6 \\ 9^{2x+y} - 3^{2x+y} - 6 = 0 $$ Let $z = 3^{2x+y}$. Then $$ z^2 - z - 6 = 0 \iff (z-3)(z+2) = 0 \iff z = 3, z \ne -2 $$ where $$ 3^{2x+y} = 3 \iff y = 1-2x. $$ Now using the second equation I get $$ \log_{x+1}(y+3) + \log_{x+1}(y+x+4) = 3 $$ Substituting $y = 1-2x$ $$ \log_{x+1}(4-2x) + \log_{x+1}(5-x) = 3. $$ Now this is the part I am stuck on , how do I solve for $x$ algebraically?

$\endgroup$
  • $\begingroup$ As a typesetting note, \times will produce the $\times$ symbol and \neq will produce the $\neq$ symbol. $\endgroup$ – JMoravitz Jan 1 '16 at 2:35
1
$\begingroup$

You finished with $$\log_{x+1}(4-2x) + \log_{x+1}(5-x) = 3$$ Go to natural logarithms (the only ones I know !); this will then write $$\frac{\log (4-2 x)}{\log (x+1)}+\frac{\log (5-x)}{\log (x+1)}=3$$ Multiply by the denominator appearing in the lhs (hoping that $x\neq -1$) and simplify.

So, $$\log (4-2 x)+\log (5-x)=3\log(x+1)$$ that is to say $$(4-2x)\times (5-x)=(x+1)^3$$ Expand and simplify to get $$x^3+x^2+17 x-19=0$$ where $x=1$ is an obvious solution. Perform the long division to get $$x^3+x^2+17 x-19=(x-1)(x^2+2 x+19)=0$$ The quadratic term does not show real solutions (in the complex domain, they would be $(x_{1,2}=-1\pm3 i \sqrt{2})$.

So $x=1$ is your solution and you were about to get it.

Happy New Year !!!!

$\endgroup$
0
$\begingroup$

Observe $$\log_{x+1}(y+3)+\log_{x+1}(y+x+4)=\log_{x+1}[(y+3)(y+x+4)]\text{.}$$ Now we have $$\log_{x+1}[(y+3)(y+x+4)] = 3$$ Take both as a power of $x+1$: $$(x+1)^{\log_{x+1}[(y+3)(y+x+4)] } = (x+1)^{3}$$ giving $$(y+3)(y+x+4)=(x+1)^{3}\text{.}$$ [since $b^{\log_{b}(x)} = x$]

$\endgroup$
0
$\begingroup$

we have $$(3^{2x+y})^2-3^{2x+y}=6$$ and $$log_{x+1}(y+3)(y+x+4)=3$$ the last equation can be written as $$(y+3)(y+x+4)=(x+1)^3$$ from the quadratic equation we get $$2x+y=1$$ can you proceed?

$\endgroup$
0
$\begingroup$

Writing the last equation

$$ \log_{x+1}(4-2x) + \log_{x+1}(5-x) = 3 $$

as

$$ \log_{x+1}[(4-2x)(5-x)] = 3 $$

you can get both term as exponents of $x+1$, so that

$$ (4-2x)(5-x) = (x+1)^3 $$

This equation can be easily solved, leading to $x=1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.